The Analysis of Students’ Computational Thinking Skills Through The Implementation of GeoGebra Integrated Student Worksheets on Motion - Diana Kamalia; Albertus Djoko Lesmono; Rif’ati Dina Handayani; Choirrudin Choirrudin (Berkala Ilmiah Pendidikan Fisika, 2024)
Computational thinking skills can help students in solving problems. Teaching materials such as student worksheets are still limited to textbooks. Physics learning can use GeoGebra to help visualise phenomena. This study aims to analyse the computational thinking ability of students through the implementation of GeoGebra integrated student worksheets on motion material on indicators of abstraction, decomposition, algorithm thinking, and generalisation. This type of research is a combination of quantitative and qualitative. Quantitative data analysis uses formula calculations to assess student worksheets. Meanwhile, qualitative data analysis uses an interactive approach by Miles and Huberman. The results showed that the students' computational thinking ability on the abstraction indicator of as many as 25 people, decomposition on as many as 20 people, and algorithmic thinking on as many as 25 people are classified as very good. This is indicated by students being able to determine important information, identify problems to be simpler, and explain steps systematically. In the generalisation indicator, students' average computational thinking ability is in a good category. In short, most students in computational thinking skills on abstraction, decomposition, and algorithm thinking are classified as very good, while the generalisation indicator is classified as good.